Effect Motivation, Competence, Work Environment, Madani Human Resources through Teacher Performance Islamic Schools - Yanti, Sri; Faizah, Ana; Nurhatisyah; Puspita Dewi, Nolla; Wibisono, Chablullah (International Journal of Psychosocial Rehabilitation, 2020)
Since the founding of the city of Batam in 1999, the vision of Batam City as the City of the World Madani has been established, with indicators to uphold the values, norms, and laws supported by the mastery of faith, science, and technology are civilized. But in reality, the educational outcomes of various schools in Batam do not all produce human resources. The study population was all elementary school instructors of Islamic Based in Batam, with a population of 380 with 5% Slovin, you obtained a sample of 195 respondents. The data were analyzed using SEM. The platform used for the examination is AMOS. Content: Effects of motivation, competence, and environment on human resources through teacher performance; motivation to positively influence the performance is not significant 0.383, competence significant as well as positive effect on the performance of 0.000, environmentally significant positive effect on the performance of 0.000, and significant positive effect performance of 0.000 against civil human resources. While the motivation of the human resources of civil effect is not significant, 0.079, the competence of the civil human resources has a significant positive effect of 0.000, and the civil environment on human resources has a significant positive effect of 0.000. Environmentally significant positive effect on the performance of 0.000 and significant positive effect performance of 0.000 against civil human resources. While the motivation of the human resources of civil effect is not significant, 0.079, the competence of the human resources Madani has a significant positive effect of 0.000, and the environment on human resources Madani has a significant positive effect of 0.000. Environmentally significant positive effect on the performance of 0.000 and significant positive effect performance of 0.000 against human resources. While the motivation of the human resources of civil effect is not significant, 0.079, the competence of human resources Madani significant positive effect of 0.000, environment on human resources Madani significant positive effect of 0.000.